THE LEGAL PROTECTION FOR DEBTORS IN THE EXECUTION OF MORTGAGE AT THE SEMARANG STATE ASSETS AND AUCTION SERVICE OFFICE - Ningsih, Ayup Suran (Jurisdictie: Jurnal Hukum dan Syariah, 2021)
One of the goals of national development in the field of economics and law is to create a just and prosperous society in accordance with Pancasila and the 1945 Constitution. One of the legal actions taken by the community for the smooth running of its business activities is to make loans or credit to financial institutions. The loan is accompanied by the provision of Mortgage on the collateral object. In the process of lending and borrowing activities from creditors to debtors, problems or defaults can occur in the future, making it possible for an auction process to be carried out. The purpose of this article is to find out and analyze the auction process by State Assets And Auction Service Office (KPKNL) in Semarang City based on Regulation of The Minister of Finance of The Republic of Indonesia (PMK) No. 213/PMK.06/2020 and to see whether the process is in line with the Indonesia Mortgage Rights Law and how the protection provided for the default debtor is. The writing method used by the author is an empirical juridical approach. The empirical juridical approach is to identify and conceptualize law as a real and functional social institution in a real-life system. The mortgage auction process done by the KPKNL Semarang based on the above regulations is appropriate and protects the debtorâ€™s rights properly.Salah satu tujuan pembangunan nasional dibidang ekonomi dan hukum adalah untuk mewujudkan masyarakat yang adil dan sejahtera sesuai dengan Pancasila dan Undang-Undang Dasar 1945. Salah satu perbuatan hukum yang dilakukan oleh masyarakat demi kelancaran kegiatan usahanya adalah dengan melakukan pinjaman atau kredit ke lembaga keuangan. Pinjaman tersebut disertai dengan pemberian Hak Tanggungan atas benda jaminannya. Dalam prosesnya kegiatan pinjam meminjamÂ dari kreditur kepada debitur ini dapat terjadi masalah atau cidera janji kedepannya, sehingga memungkinkan untuk dilakukannya proses lelang. Penulisan artikel ini bertujuan untuk mengetahui dan menganalisis proses lelang oleh Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) di Kota Semarang berdasarkan PMK No. 213/PMK.06/2020 dan untuk melihat apakah proses tersebut sudah sejalan dengan Undang-Undang Hak Tanggungan serta bagaimana perlindungan yang diberikan bagi debitur wanprestasi tersebut. Metode penulisan yang digunakan penulis ialah pendekatan yuridis empiris. Pendekatan yuridis empiris ialah mengidentifikasi dan mengkonsepsi hukum sebagai institusi sosial yan riil dan fungsional dalam sistem kehidupan yang nyata. Proses lelang hak tanggungan yang dilakukan oleh KPKNL Semarang berdasarkan peraturan tersebut diatas sudah sesuai dan melindungi hak debitur dengan baik.